2019
DOI: 10.14710/nmjn.v9i1.22253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Islamic Spiritual Mindfulness on Stress among Nursing Students

Abstract: Background: Academic stress is a major problem that often occurs in nursing students. Islamic spiritual mindfulness (ISM) is an adaptive coping strategy used to mitigate various negative psychological reactions to respond stressors experienced by the body to build self-awareness that any problems experienced today are the scenario of Allah.Purpose: This study aimed to determine the effects of Islamic spiritual mindfulness therapy to reduce stress.Methods: This study used a pre-post quasi-experimental design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 11 publications
1
26
0
6
Order By: Relevance
“…Even though evidence showed that mindfulness is an effective strategy for people with schizophrenia, such study is rarely implemented in Indonesia. A recent study showed that mindfulness can reduce the anxiety level among nursing students (Munif, Poeranto, & Utami, 2019). Another study indicated that mindfulness therapy could reduce the risk of violence and control the emotion among patients with schizophrenia (Sari & Dwidiyanti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though evidence showed that mindfulness is an effective strategy for people with schizophrenia, such study is rarely implemented in Indonesia. A recent study showed that mindfulness can reduce the anxiety level among nursing students (Munif, Poeranto, & Utami, 2019). Another study indicated that mindfulness therapy could reduce the risk of violence and control the emotion among patients with schizophrenia (Sari & Dwidiyanti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of them is mindfulness. This therapy aims to build selfawareness, to accept whatever conditions faced at present with full acceptance and to build focus in solving problems (Munif, Poeranto & Utami, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness is an exercise in building selfawareness to accept the conditions experienced at present, meaning that someone is able to set goals and to focus in solving problems that he encountered (Kabat-Zinn, 2012). The purpose of mindfulness is to build selfawareness, to accept any conditions faced at present with full acceptance and to build focus in solving problems (Munif, Poeranto & Utami, 2019a). Having the ability to manage stressors as early as possible can increase students' adaptive coping toward the stress response experienced by the body.…”
Section: Introductionmentioning
confidence: 99%
“…(Adeosun, 2013) Penelitian yang sudah dilakukan dan dipublikasikan untuk mengatasi keadaan stres menggunakan intervensi mindfulness spiritual Islam sejauh ini adalah pengaruh intervensi mindfulness spiritual Islam terhadap tingkat stres mahasiswa dengan hasil penelitian menunjukkan bahwa mindfulness spiritual Islam signifikan mnurunkan keadaan stres yang terjadi. (Munif, Poeranto, & Utami, 2019) Penelitian untuk mengatasi tingkat stres di area yang lebih luas terutama pada keluarga pasien skizofrenia menggunakan intervensi mindfulness spiritual Islam belum pernah dilakukan penelitian. Melalui penelitian ini, peneliti akan menggunakan intervensi mindfulness spiritual Islam untuk mengatasi keadaan stres yang terjadi pada keluarga pasien skizofrenia.…”
Section: Pendahuluanunclassified